Polskie uczelnie wyższe lat międzywojennych i ich społeczności w relacji prasowej „Ilustrowanej Republiki” - Michalska, Iwonna (Biuletyn Historii Wychowania, 2018)
“Ilustrowana Republika” was a daily published in Łódź in 1925–1939. Apart from the news, it published economic, social, cultural, educational, and sports information as well as materials on tertiary education. The issue of higher education was raised in over 440 articles and notes, which included information on the Łódź and other Polish universities. Journalists wrote about activities which aimed at making Łódź a university city and about more important events from the life of Polish universities. Fewer publications focused on academic issues; however, a great part of articles showed individual and atypical student conduct sometimes hard to accept such as suicidal attempts, conflicts with the law, organising anti-Semitic manifestations by right-wing students for almost the entire Interwar period. This work does not provide a complete picture of tertiary education or the academic community before WWII as it presents only facts and events described in the newspaper. However, it may be useful as a basic source for more comprehensive works concerning higher education in the past.